2018
DOI: 10.1007/s11934-018-0818-8
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Stent Discomfort and Its Management

Abstract: Though it has been extensively studied, the exact cause of stent-related symptoms remains unknown but is likely related to irritation of the bladder by the distal curl of the stent and reflux of urine through the stent up to the renal pelvis and transmission of high pressures associated with this. Recent research has focused on trying to modify stents including the creation of drug eluting stents as well as preventing symptoms with intravesical instillation of medications in the operative room at the time of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 50 publications
1
32
0
2
Order By: Relevance
“…Ureteral stent is the most commonly used medical implant for urological surgery. It is widely used in clinical practice because it can relieve urinary tract obstruction, drain urine, and protect renal function [14,15]. After PCNL operation, ureteral stent is usually retained for 4-6 weeks, but some patients need to keep ureteral stent for a long time because of the complex condition.…”
Section: Discussionmentioning
confidence: 99%
“…Ureteral stent is the most commonly used medical implant for urological surgery. It is widely used in clinical practice because it can relieve urinary tract obstruction, drain urine, and protect renal function [14,15]. After PCNL operation, ureteral stent is usually retained for 4-6 weeks, but some patients need to keep ureteral stent for a long time because of the complex condition.…”
Section: Discussionmentioning
confidence: 99%
“…As the prevalence of stent-related symptoms such as flank pain and irritative voiding symptoms is relatively high [9], the necessity of stenting a reimplanted ureter is under debate. Brandell et al [10] reviewed 34 patients with VUR who underwent laparoscopic ureteral reimplantation (LUR), of which 20 patients were "stentless."…”
Section: Discussionmentioning
confidence: 99%
“…Considering the stent symptoms, it is a difficult condition to treat, as the mechanism is not well known, and treatment includes alpha‐blockers, anticholinergics, anti‐inflammatory medications and narcotic pain medications . In contrast, a retrospective study has shown that a postoperative ureteral stent is not necessary after fURS using an access sheath in pre‐stented patients, leading to the thought of not inserting a stent, which could avoid patients having stent symptoms, as well as preventing forgotten stents…”
Section: Ureteroscopy and Retrograde Intrarenal Surgerymentioning
confidence: 99%